The Role of Religiosity on The Happiness of Students in Padang - Ifani Candra; Krisnova Nastasia; Suparmi Suparmi (Jurnal Syntax Transformation, 2024)
This research aims to determine the relationship between religiosity and happiness in students at SMK Negeri "X" Padang. The variables in this research are religiosity (X) and happiness (Y). The sampling technique in this research used a stratified random sampling technique. The total sample were 182 people. The measuring instruments used in this research are the religiosity scale and happiness scale. The data analysis method used for hypothesis testing in this research is using Pearson product moment (Pearson) correlation which was carried out with the help of IBM SPSS version 21.0, which shows that the correlation coefficient value is r=0.723 with a sig value=0.000, because the value (p) sig 0.000, because the value (p) sig 0.000 <0.01 which means there is a very significant relationship between religiosity and happiness in a positive direction, meaning that the higher the religiosity, the higher the happiness. On the other hand, the lower the religiosity, the lower the happiness of students at SMK Negeri "X" Padang. This means that the research hypothesis is accepted. The effective contribution of the religiosity variable to happiness is 52%.